Physical activity and health-related quality of life among staff in UiTM Pahang / Wan Mohd Norsyam Wan Norman , Nurul Ain Muhammad Rafiai and Shazana Ismail - Wan Norman, Wan Mohd Norsyam; Muhammad Rafiai, Nurul Ain; Ismail, Shazana (2013)
Physical activity plays an important role in promoting health and increasing the quality of life for all segments of society. Therefore. this cross-sectional study was conducted to determine the relationship between physical activity status and health- related quality of life (HRQOL) among the staff in UiTM Pahang. A questionnaire was distributed to 65 staff during "Health-Screening Program" which was organized by Health Unit, UiTM Pahang. The physical activity index (PAI) was determined using General Practice Physical Activity Questionnaire (GPPAQ) while health-related quality of life was assessed by using self-rating Center for Disease Control and Prevention HRQOL-4 tools. The association between gender and physical activity index were observed while no association had been observed between physical activity index and health status measure and other three HRQOL measure (recent physical health, recent mental health and recent activity limitation) among staff in UiTM Pahang. In conclusion, the staff in UiTM Pahang had a high self-rating of HRQOL regardless the physical activity index.